Landscape of mortality during and within thirty days after non-palliative radiotherapy across eleven major cancer types. (February 2022) - Xiang, Michael; Raldow, Ann C.; Pollom, Erqi L.; Steinberg, Michael L.; Kishan, Amar U.
Highlights: The overall rate of peri-RT mortality was 2.46% from 2004 through 2016. Rates substantially downtrended over time for most (but not all) cancer types. Major predictors were age, comorbidity, male sex, stage, lack of private insurance. More conformal RT technique and higher facility volume were moderately protective. Black patients had increased peri-RT mortality for breast, lymphoma, and GI cancers. Abstract: Background and Purpose: Peri-RT mortality (death during or within 30 days of non-palliative radiotherapy) has been historically overlooked, and rates and risk factors are unclear. Materials and Methods: Patients with non-metastatic cancer, treated with non-palliative external beam radiation (RT) 2004–2016, were identified in the National Cancer Database for 11 cancer types: breast, prostate, non-prostate genitourinary, bone/soft tissue, gynecological, head/neck, lymphoma, gastrointestinal (GI), small cell lung, non-small cell lung, and central nervous system (CNS). Multivariable logistic regression was used to identify predictors of peri-RT mortality controlled for 17 covariates, including patient, tumor, and treatment factors. Results: Approximately 1.53 million patients were identified. Peri-RT mortality was 2.46% overall, spanning two orders of magnitude from 0.14% for breast to 8.52% for CNS. Peri-RT mortality steadily improved from 3.13% in 2004 to 1.78% in 2016 ( P  < .0001). Major predictors of peri-RT mortality included age, baseline comorbidity, male sex, and stage ( P  < .0001). Conversely, higher patient volume at the treating facility and use of more conformal RT planning techniques were moderately protective ( P  < .0001). Racial disparities varied based on disease site, as Black patients had increased peri-RT mortality for breast, lymphoma, and GI cancers, but not for other cancer types. Lack of private insurance was associated with substantially increased peri-RT mortality regardless of cancer type. Conclusion: Peri-RT mortality varied considerably according to multiple factors. Sociodemographic differences highlight areas of health disparities and opportunities for quality improvement. Early recognition of patients at increased risk may facilitate implementation of closer monitoring or other preventive measures.